Re-Viewing Resistance in Namibian History - Silvester, Jeremy (Book collections on Project MUSE., 2015)
Re-Viewing Resistance in Namibian History brings together the work of experienced academics and a new wave of young Namibian historians - architects of the past - who are working on a range of public history and heritage projects, from late nineteenth century resistance to the use of songs, from the role of gender in SWAPO's camps to memorialisation, and from international solidarity to aspects of the history of Kavango and Caprivi. In a culturally and politically diverse democracy such as Namibia, there are bound to be different perspectives on the past, and history will be as plural as the h.